A Robust Metal–Organic Framework for Dynamic Light‐Induced Swing Adsorption of Carbon Dioxide. Issue 32 (6th July 2016) - Li, Haiqing; Martinez, Marta Rubio; Perry, Zachary; Zhou, Hong‐Cai; Falcaro, Paolo; Doblin, Christian; Lim, Seng; Hill, Anita J.; Halstead, Barry; Hill, Matthew R.
Abstract: Adsorbents for CO2 capture need to demonstrate efficient release. Light‐induced swing adsorption (LISA) is an attractive new method to release captured CO2 that utilizes solar energy rather than electricity. MOFs, which can be tailored for use in LISA owing to their chemical functionality, are often unstable in moist atmospheres, precluding their use. A MOF is used that can release large quantities of CO2 via LISA and is resistant to moisture across a large pH range. PCN‐250 undergoes LISA, with UV flux regulating the CO2 desorption capacity. Furthermore, under UV light, the azo residues within PCN‐250 have constrained, local, structural flexibility. This is dynamic, rapidly switching back to the native state. Reusability tests demonstrate a 7.3 % and 4.9 % loss in both adsorption and LISA capacity after exposure to water for five cycles. These minimal changes confirm the structural robustness of PCN‐250 and its great potential for triggered release applications. Abstract : LISA sets it free : Highly efficient photoswitching of CO2 uptake and release in a robust metal–organic framework (MOF) is achieved through intermittently exposing the MOF to UV light. The release method, which does not require electricity, is light‐induced swing adsorption (LISA; see figure).